(untitled) (Asian Journal of Social Science Studies, 2017)
Fixed assets are the assets of permanent nature used in the operation of a business. These assets are earning assets and provide the basis for the firm’s earning power and value. Due attention must be given to the management of fixed assets as they represent sizable outlay and involve the long-term financial commitment. A systematic blending of current and fixed assets into a profitable combination is a challenging task to the financial management. An analysis on the financing pattern and utilization of fixed assets is, therefore, vital for the management of a business enterprise. The financing pattern and utilization of fixed assets of Tata Steel Ltd., the selected company have been studied with the help of several statistical measures during the period from 2011-12 to 2015-16. The study reveals the sufficiency of owners’ funds to finance fixed assets requirements and that the company had also enough long-term funds to finance the entire fixed assets as well as part of current assets. The pace of expansion in gross block on sales was not impressive in the years of study. Apart from this, slow increase in the indices of depreciation points out that overall provision for depreciation was moderate in the company under reference.